Selective oxidations over zeolite- and mesoporous silica-based catalysts: selected examples - Ratnasamy, Paul; Srinivas, Darbha (Catalysis Today, 2009)
Selective oxidation of hydrocarbons/terpenes in the liquid phase are reported over three categories of zeolite- and mesoporous silica-based catalysts: (1) transition metal complexes (metal phthalocyanines, copper acetate dimers and Co/Mn acetate trimer) encapsulated in zeolite-Y, (2) transition metal complexes (Mn-Salen), grafted on SBA-15, and (3) transition metal ions in framework positions of zeolites and mesoporous molecular sieves like Ti-silicates. Upon heterogenization, the metal complexes exhibited enhanced catalytic acitivity/selectivity. The causes for the enhanced catalytic activity/product selectivity have been explored. Dimer formation (copper acetate) or geometric distortion in the zeolite cavities (metal phthalocyanines) and consequent changes in energy levels and redox potentials are shown to modify the catalytic activity (in the selective oxidation of hydrocarbons) of the encapsulated metal complexes. In the case of Mn-Salen grafted on SBA-15, increasing the acidity of the siliceous surface (by -SO(3)H groups, for example) leads to a more facile reduction of the Mn ions and, thereby, enhanced catalytic activity in the selective epoxidation of limonene. When Ti ions are introduced in framework positions, reactive metal-oxo species are formed on contact with H(2)O(2) or O(2), Which influence the mode of O-O cleavage (heterolytic/homolytic) and product selectivity. The structure-function relationships in these catalysts are reported. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Mn-Salen; Oxidation of hydrocarbons and limonene; Reactive oxo species; Selective oxidation; Titanosilicates; Zeolite-encapsulated metal complexes

Synthesis of framework Ti-substituted, 3-D hexagonal, mesoporous Ti-SBA-12 for selective catalytic oxidation - Kumar, Anuj; Srinivas, Darbha; Ratnasamy, Paul (Chemical Communications, 2009)
Framework Ti-substituted, 3-D hexagonal mesoporous, Ti-SBA-12, obtained for the first time by direct hydrothermal synthesis, oxidises bulky molecules such as cyclohexene and cyclooctene to the epoxides with >96% selectivity at high conversion levels (>60%).

Selective oxidation of cyclic olefins over framework Ti-substituted, three-dimensional, mesoporous Ti-SBA-12 and Ti-SBA-16 molecular sieves - Kumar, Anuj; Srinivas, Darbha (Catalysis Today, 2012)
Framework Ti-substituted, three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, were prepared by direct hydrothermal synthesis method. These catalysts showed catalytic activity higher than the hitherto known titanosilicates for the oxidation of cyclic olefins (cyclohexene and cyclooctene) with tert.-butyl hydroperoxide. An epoxide selectivity of 100% and olefin conversion greater than 92% were obtained. Cubic Ti-SBA-16 with interconnected cage-like mesopore structure was more active than hexagonal Ti-SBA-12. X-ray diffraction and diffuse reflectance UV-vis, Fourier transform infrared, Raman and electron paramagnetic resonance spectroscopies provided evidence for the substitution of Ti4+ (for Si4+) in the framework locations. The catalytic activity correlated with the concentration of framework-substituted, tetrahedral Ti4+ ions. Easy accessibility of the active sites and the three-dimensional mesoporous structure are the possible causes for the superior activity of these titanosilicate catalysts. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Epoxidation of cyclic olefins; mesoporous materials; Molecular sieves; Selective oxidation; Ti-SBA-12; Ti-SBA-16; Titanosilicates

Spectroscopy and catalytic activity study of gold supported on barium titanate nanotubes for styrene epoxidation - Nepak, Devadutta; Srinivas, Darbha (Applied Catalysis A-General, 2016)
Gold (0.5-5 wt.%) supported on barium titanate nanotubes (Au/BaTNT) were prepared, characterized and for the first time, investigated as catalysts for selective oxidation of styrene with oxygen (O-2 or H-2 + O-2) and peroxides (H2O2 or TBHP). Conversion of styrene enhanced when H-2 was co-added to O-2 in the reactions. Au/BaTNT activated O-2 and H-2 and produced H2O2 in situ for use in oxidations. Peroxides were found better oxidants than O-2. At optimized conditions, styrene oxide selectivity of 80.1 wt.% at styrene conversion of 60.5 wt.% was achieved over Au(1 wt.%)/BaTNT using TBHP. Au particles (5.0-7.4 nm) were dispersed and decorated on the walls of BaTNT. They exhibited superior performance to the known Au catalysts in styrene oxidation. Reactive oxygen species formed during oxidation reactions were followed with in situ spectral characterizations (diffuse reflectance UV-vis and FT -Raman). Au/BaTNT was reusable in four recycles with little loss in catalytic activity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Au Nanoparticles; reactive oxygen species; spectroscopy; Styrene Oxidation; Titanate nanotubes

Selective and reusable Pt-WO x /Al 2 O 3 catalyst for deoxygenation of fatty acids and their esters to diesel-range hydrocarbons - Janampelli, Sagar; Srinivas, Darbha (Catalysis Today, 2017)
Tungsten oxide promoted platinum catalysts (Pt-WOx/Al2O3) of varying composition were prepared by wet impregnation method and reduced in hydrogen atmosphere. X-ray powder diffraction and photoelectron spectroscopy revealed that Pt is completely reduced to metallic state while tungsten is in +6 and +5 oxidation state. Pt crystallite and particle sizes increased (from 1.2 to 1.4 nm and 2.5 to 3 nm, respectively) in presence of WOx (CO-chemisorption and transmission electron microscopy). Tungsten addition augmented strong acid sites. It enhanced significantly the catalytic activity of Pt/Al2O3 in deoxygenation of fatty acids and their methyl esters. Tungsten altered the reaction pathway from decarbonylation/decarboxylation to hydrodeoxygenation. A catalyst with 4 wt% Pt and 8 wt% W exhibited high catalytic performance. Complete conversion of oleic acid and octadecane product selectivity in the range 67.1 − 80.8% was obtained. Pt-WOx/Al2O3 is a stable and reusable fatty acid deoxygenation catalyst.
Keywords: biofuels; Deoxygenation; Diesel-range hydrocarbons; Fatty acids; Pt catalyst